The oncogenic potential of human papillomaviruses: a review on the role of host genetics and environmental cofactors (2007)
Human papillomaviruses (HPVs), with over 100 genotypes, are a very complex group of human pathogenic viruses. In most cases, HPV infection results in benign epithelial proliferations (verrucae). However, oncogenic types of HPV may induce malignant transformation in the presence of cofactors. For example, over 99% of all cervical cancers and a majority of vulval, vaginal, anal and penile cancers are the result of oncogenic HPV types. Such HPV types have been increasingly linked to other epithelial cancers involving the skin, larynx and oesophagus. Although viral infection is necessary for neoplastic transformation, evidence suggests that host and environmental cofactors are also required. Research investigating HPV oncogenesis is complex and quite extensive. The inability to produce mature HPV virions in animal models has been a major limitation in fully elucidating the oncogenic potential and role of associated cofactors in promoting malignant transformation in HPV‐infected cells. We have reviewed the literature and provide a brief account of the current understanding of HPV oncogenesis, emphasizing the role of genetic susceptibility, immune response, and environmental and infectious cofactors.